Molecular characterization and phylogenetic analysis of highly pathogenic H5N1 clade 2.3.4.4b virus in Bosnia and Herzegovina - Goletic, Sejla; Softic, Adis; Omeragic, Jasmin; Koro-Spahic, Amira; Kapo, Naida; Sabic, Emina; Kasagic, Dragan; Goletic, Teufik (Frontiers in Veterinary Science, 2023)
Influenza A virus continues to represent a growing problem affecting mainly birds, but with an increasing number of mammal transmission events reported each year. Timely detection, reporting of cases, and phylogenetic and epidemiological analysis remain crucial to the prompt implementation of mitigation measures. Nevertheless, molecular characterization and phylogenetic analysis of influenza A viruses originating from all confirmed cases have not been systematically performed in all parts of the world. In this study, we investigated a sample originating from a mute swan that died in November 2021 from in the northern part of Bosnia and Herzegovina with RT-qPCR and whole genome sequencing using ONT MinION. It was diagnosed as a highly pathogenic Influenza A virus, subtype H5N1 of 2.3.4.4b clade, and phylogenetic analysis revealed high sequence homology with other European HPAI H5N1 sequences at the time. The notable detected mutations in HA (N110S and T139P) and NA genes (H155Y), that facilitate the host specificity shift and enable the resistance to some antiviral drugs respectively, underscore the necessity of virus evolution surveillance. Therefore, the rapid dissemination of information, including virological and molecular data, is essential for the introduction of tailored prevention measures for infected animals, providing clearer insight and better awareness of a potential public health threat.